2011
DOI: 10.1074/mcp.m110.004994
|View full text |Cite
|
Sign up to set email alerts
|

Complex Networks Govern Coiled-Coil Oligomerization – Predicting and Profiling by Means of a Machine Learning Approach

Abstract: Understanding the relationship between protein sequence and structure is one of the great challenges in biology. In the case of the ubiquitous coiled-coil motif, structure and occurrence have been described in extensive detail, but there is a lack of insight into the rules that govern oligomerization, i.e. how many α-helices form a given coiled coil. To shed new light on the formation of two- and three-stranded coiled coils, we developed a machine learning approach to identify rules in the form of weighted ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…7 and its exemplar sequence. Of the top five trimer patterns (Mahrenholz et al, 2011), three occur prominently in trimer cluster no. 3: E..Ie, E....Kb and I...Id, two of which occur twice or more often in the cluster and in the corresponding exemplar.…”
Section: Example: Clustering Coiled Coilsmentioning
confidence: 99%
See 4 more Smart Citations
“…7 and its exemplar sequence. Of the top five trimer patterns (Mahrenholz et al, 2011), three occur prominently in trimer cluster no. 3: E..Ie, E....Kb and I...Id, two of which occur twice or more often in the cluster and in the corresponding exemplar.…”
Section: Example: Clustering Coiled Coilsmentioning
confidence: 99%
“…Mahrenholz et al (2011) have studied which sequence characteristics determine whether a given coiled coil segment tends to form a dimer or trimer. Mahrenholz et al (2011) found out that pair interactions of amino acids are the key to understanding coiled coil oligomerization and, consequently, propose a custom string kernel based on pair interactions, the coiled coil kernel, upon which they base their prediction tool PrOCoil.…”
Section: Example: Clustering Coiled Coilsmentioning
confidence: 99%
See 3 more Smart Citations